Automatic digital scaling of analog computers - Glaum, Frederick Charles (Department of Electrical Engineering, 2016)
The purpose of this work is to develop an algorithm for use on a small digital computer in the conversational mode. This algorithm to scale and determine the patching configuration for the simulation of any system on an analog computer. Further, this should be in a form suitable for the implementation of automatic patching in a hybrid computer which contains the necessary switching matrix and hardware. The method of solution chosen here relies heavily on modern control theory, and in this lies both its strength and its weakness. The advantage of the method is that it forms a direct link between the State Space representation of a system and the analog computer simulation of that system. The chief disadvantage is that it is cumbersome in the handling of non-linear systems. The method can be divided broadly into two sections: 1) Digital simulation of system in order to determine the maximum values of all variables. 2) Scaling and analog set-up.